Upaya Meningkatkan Hasil Belajar Bernyanyi Siswa Dalam Pembelajaran Seni Budaya Melalui Metode Latihan Di Kelas VII A Smp Pembangunan Laboratorium UNP - fatia Apriliana Yudha; Ardipal (Universitas Negeri Padang, 2023)
Throughout the learning process, several students didn't participate actively. Only a small number of women have the ability to perform guru tasks and a small number can perform theme tasks. In addition to that, some women can only listen to one song that their teachers give them and that is playing while they are bernying, which is only one of many songs they can listen to. The current investigation used penelitian tindakan kelas (PTK), which was carried out through a structured procedure. Methodology of instruction has improved student performance in seni budaya classrooms in kelas VII A of the SMP Pembangunan Laboratorium UNP.